Correlation between psoriasis' severity and waist-to-height ratio - Gleison Vieira Duarte; Larissa Porto da Silva (Sociedade Brasileira de Dermatologia, 2014)
In the absence of ideal biomarkers, the research for clinical markers correlated to the severity of psoriasis and/or its comorbidities becomes crucial. Recently, studies have shown positive correlation between body mass index and prevalence and severity of psoriasis. Abdominal circumference showed stronger correlation with disease severity than body mass index. We evaluated the waist-to-height ratio in a sample of 297 adult patients with psoriasis and observed that it has a significant correlation with body mass index and PASI, and together with body mass index allows the identification of central obesity, reducing its subdiagnosis.